Uterine carcinosarcoma with microsatellite instability - does immunotherapy modify the therapeutic scenario? A case report and literature review - Diocesio Alves Pinto Andrade; Eduardo Paulino; Isabela Panzeri Carlotti Buzatto; Danilo Tadao Wada; Warne Pedro Andrade; Andreia Cristina Melo; Angelica Nogueira-Rodrigues (Brazilian Journal of Oncology)
Carcinosarcomas were reclassified by World Health Organization as high-grade uterine carcinomas in 2014. Due to its rare histology, comprising only 5% of uterine carcinomas, there is a small representation of this tumor in studies that evaluate metastatic uterine carcinomas treatment. In 2022, the treatment of metastatic uterine carcinomas has changed dramatically with the inclusion of immunotherapy in the therapeutic arsenal, either as a monotherapy or in combination with lenvatinib. The status of microsatellites is paramount in the therapeutic decision for this tumor; carcinosarcoma patients haven't been included in randomized trials so far. Here we report the case of a 60-year-old woman diagnosed with recurrent carcinosarcoma metastatic to the liver and pelvis. Immunohistochemistry demonstrated microsatellite instability (loss of MLH1 and PMS2 nuclear staining). She received immunotherapy with pembrolizumab every three weeks as monotherapy and after 4 cycles, she achieved a complete radiological response in the liver and a partial response in the pelvis.